Kilka uwag na temat doradcy rady nadzorczej spółki akcyjnej - Delczyk, Dominik (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
The paper concerns selected aspects related to the regulations concerning advisors to the supervisory board of a joint-stock company. The paper draws attention to several imperfections of the current regulations. It also expresses a de lege ferenda postulate that criteria of competency and experience should be introduced as the condition for the performing of performing the function of an advisor to the supervisory board in a company in which the State Treasury or a local government unit holds shares.
Keywords: doradca rady nadzorczej; rada nadzorcza; spółka akcyjna